Protective role of vitamin E on drug induced neuropathy - Roy, Regina; Hema, C. G.; Geetha, N.; Indla, Ravi; Chinnathampi, Thangam (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The objective of this study was to look into the protective role of vitamin E (Vit.E) on drug‑induced neuropathy. Methods: The study involved 18 albino rats; rats were divided into 3 Groups; Group 1 ‑ control (n = 6), Group 2 - anti‑leukemic drugs treated rats (n = 6), Group 3 - anti‑leukemic drugs and Vit.E treated rats (n = 6). Anti‑leukemic drugs which included vincristine (VCR), L‑asparaginase (L‑Asp), doxorubicin (ADR), prednisolone (PDN), were administered to Group 2 and Group 3 rats according to acute lymphoblastic leukemia treatment regimen (MCP841). Group 3 rats were given in addition to the anti‑leukemic drugs, Vit.E (100 mg/kg bodyweight/orally) daily. Tests for neuropathy were done using tail clip method, tail flick method, hot plate method on the 2nd week and tail clip method on 4th week of therapy. Results: At the end of 2nd week by tail clip method and tail flick method the mean reaction time of the anti‑leukemic drugs alone treated group (Group 2) was increased showing the development of neuropathy. The mean reaction time of the anti‑leukemic drugs + Vit.E treated group (Group 3) showed a reduction in the reaction time, showing the protective role of Vitamin E. Hot plate method done at the end of 2nd week showed a decrease in mean reaction time in Group 2 rats compared with Group 3. This could be due to the hyperthermalgesia by VCR. Group 3 was protected by Vit.E. Conclusion: Observations showed a protective role of Vit.E on drug induced neuropathy.